Implimentasi Supervisi Klinis dalam Meningkatkan Kompetensi Profesional Pendidik Era Digital Di MTS At-Tibyan Deli Serdang - Latifatuz Zahra; Mufidah Zahro; Muhammad Iqbal (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to analyze the implementation of clinical supervision at MTS At-Tibyan Deli Serdang in digital era and its implications for improving teachers’ professional competence and the quality of students’ learning outcomes. This research employed a qualitative approach with field research design and hybrid data collection techniques, including online interviews, direct classroom observations, and analysis of digital supervision documents. Informants were selected using purposive sampling, involving supervisors, supervised teachers, and curriculum staff. Data were analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings indicate that digital-based clinical supervision utilizing Google Spreadsheet enhances the effectiveness of observation processes, transparency of assessment, and efficiency in supervision data management. The supervision process includes natural classroom observations, individualized follow-up, and continuous collective training. The results also show a significant improvement in teachers’ professional competence, including teaching preparedness, use of digital learning media, classroom management, and the ability to design active learning. Furthermore, clinical supervision contributes to increased student participation, motivation, and conceptual understanding through the application of more interactive and constructive learning methods. Thus, digital-based clinical supervision proves to be an effective strategy for improving teaching quality in the digital era.